دەرکەوتنی دیمەنی ژن لەسەر مۆرە لولەییەکانی سەردەمی خوری لە شاری ئورکێش (سەدەکانی ٢٣و٢٢ی پ.ز. - عبدالصمد, د.رافدة عبداللە; سیدە, ژینۆ عبداللە (Sulaimani Journal for Humanities, 2024)
Cylinder Seals are an important source of artistic research. Through engraving on seals, we can learn about all eras because they reflect all aspects of society's life. The seal engravers engraved these subjects at the request of the seal owner, whether it was the daily life of the community or religious ceremonies, or religious scenes or events and legends that belonged to that community or the previous community and inherited to later generations. Some seals have specific symbols to put their stamps on personal letters and business transactions, as well as a protector for the pots in which valuables were placed to protect them from touch. In this paper, we deals with the appearance of women on the cylinder seals of the Hurrian period in the City of Urkesh, and we will also highlight their roles, positions and works that they have done in this paper.